Content validation of the self-care assessment scale for heart failure patients - Sherida Karanini Paz de Oliveira; Francisca Elisângela Teixeira de Lima (Rev Rene)
Objective: to build and validate the content of the Self-Care Assessment Scale for Heart Failure Patients. Methods: methodological study based on psychometry. A search was carried out in five databases resulting in 63 articles that guided the preparation of a preliminary instrument. Content was validated by eight judges who assessed the adequacy of each item according to the criteria: clarity, precision and relevance. Results: there was an agreement among judges of 0.896 (p=0.001), and the validity of the content of the scale was confirmed. The instrument consisted of 20 items distributed into six dimensions: Nutrition (4 items), Activity and rest (3 items), Perception and cognition (3 items), Health promotion (6 items), Stress tolerance (2 items) and Roles and Relationships (2 items). Conclusion: the instrument obtained a satisfactory content validity index which shows that the scale is representative of the construct content.